SOSIALISASI TENTANG PENERAPAN PROTOKOL KESEHATAN PENCEGAHAN COVID-19 DI KABUPATEN BATU BARA PROVINSI SUMATERA UTARA - Felix Kasim; Sri Melda Bangun; Anggi Isnani Paranduri; Henri Gudmen Sihite; Ika Nur Saputri; Kuat Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The COVID-19 pandemic has become a world health problem since the end of 2019, this case is increasing and spreading rapidly throughout the world, including Indonesia. Batu Bara Regency is one of the districts experiencing an increase in confirmed cases of COVID-19. The purpose of this paper is to provide socialization about the implementation of the COVID-19 prevention health protocol in Batu Bara Regency, North Sumatra Province. The method of implementing the activity is in the form of observation and socialization about the implementation of the COVID-19 prevention health protocol in the community. Based on the results of the activities that have been carried out, the community has a better understanding of health protocols in prevention efforts, it is hoped that it will have an impact on changing people's behavior to better comply with and implement the COVID-19 prevention health protocol so that there will be a significant decrease in cases.